2013
DOI: 10.1016/j.bpj.2012.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Photon Shot Noise Limits on Optical Detection of Neuronal Spikes and Estimation of Spike Timing

Abstract: Optical approaches for tracking neural dynamics are of widespread interest, but a theoretical framework quantifying the physical limits of these techniques has been lacking. We formulate such a framework by using signal detection and estimation theory to obtain physical bounds on the detection of neural spikes and the estimation of their occurrence times as set by photon counting statistics (shot noise). These bounds are succinctly expressed via a discriminability index that depends on the kinetics of the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(172 citation statements)
references
References 55 publications
(95 reference statements)
1
171
0
Order By: Relevance
“…However, even these ratiometric approaches still require additional post hoc analysis to remove the properly scaled hemodynamic components from the recorded signals, which has been shown to be a nontrivial issue. 19,64 For the non-FRET-based imaging methodology of ArcLight, we found that the ongoing hemodynamic noise required additional post hoc processing through Off-ROI subtraction to gain access to single-trial responses in the S1 cortex of the anesthetized mouse.…”
Section: Arclight Excitation Causes Substantial Hemodynamic Noise In mentioning
confidence: 99%
“…However, even these ratiometric approaches still require additional post hoc analysis to remove the properly scaled hemodynamic components from the recorded signals, which has been shown to be a nontrivial issue. 19,64 For the non-FRET-based imaging methodology of ArcLight, we found that the ongoing hemodynamic noise required additional post hoc processing through Off-ROI subtraction to gain access to single-trial responses in the S1 cortex of the anesthetized mouse.…”
Section: Arclight Excitation Causes Substantial Hemodynamic Noise In mentioning
confidence: 99%
“…33 This will reduce the fidelity of spike detection since in the optical shotnoise-limited regime this fidelity scales as the square root of the fluorescence intensity. 34 In principle, the lower quantum yield value can be offset with higher excitation intensity.…”
Section: Voltage Sensitivity Of Type-ii Semiconductor Nanoparticlesmentioning
confidence: 99%
“…35,36 To explore how well nanocrystals permit spike detection, we applied a recently developed theoretical framework that quantifies the capability to discriminate neural spikes optically in the regime of shotnoise-limited photon detection. 34 This framework allowed us to assess the contributions made to the spike detection fidelity by indicator attributes such as brightness, voltage sensitivity, and labeling density, as well as from the optical capabilities of the microscope, such as collection efficiency, frame rate, and excitation intensity. Our analysis helps guide experimental design and motivates rational improvements to nanocrystal indicators.…”
Section: Fidelity Of Action Potential Detection Using Nanocrystalsmentioning
confidence: 99%
“…In the initial optical system, a fundamental noise source is photon shot noise, which results from the random nature of photon emission [25]. Photon shot noise is random, with a Poisson distribution of the number of detected photons [26]. Although some factors, such as the integration time and quantum efficiency of the detector, influence photon shot noise, its intrinsically random nature makes photon shot noise impossible to avoid.…”
Section: Summary Of Noise In Libs Systemmentioning
confidence: 99%